Validation methods for encapsulated faecal microbiota transplantation: a scoping review - Nina Rågård; Simon Mark Dahl Baumwall; Sara Ellegaard Paaske; Mette Mejlby Hansen; Katrine Lundby Høyer; Susan Mikkelsen; Christian Erikstrup; Jens Frederik Dahlerup; Christian Lodberg Hvas (Therapeutic Advances in Gastroenterology)
Faecal microbiota transplantation (FMT) is increasingly used for diseases associated with a disrupted intestinal microbiome, mainly Clostridioides difficile infection. Encapsulated FMT is a patient-friendly application method that improves accessibility and convenience. Capsule processing may be standardised, but validation protocols are warranted. This review aimed to describe published validation methods for encapsulated FMT. Original studies reporting using encapsulated faecal formulations were included, regardless of indication. Studies were excluded if they did not address processing and validation or used non-donor-derived content. We conducted a comprehensive scoping review, implementing a systematic search strategy in PubMed, Embase and Web of Science. Processing data and validation methods were registered during full-text analysis and combined to create an overview of approaches for assessing quality in encapsulated FMT processing. The searches identified 324 unique studies, of which 44 were included for data extraction and analysis. We identified eight validation covariables: donor selection, pre-processing, preservation, oxygen-sparing processing, microbial count, viability, engraftment and clinical effect outcomes, from which we constructed a model for quality assessment of encapsulated FMT that exhaustively categorised processing details and validation measures. Our model comprised three domains: (1) Processing (donor selection and processing protocol), (2) Content analysis (microbiota measures and dose measures) and (3) Clinical effect (engraftment and clinical outcomes). No studies presented a reproducible capsule protocol; their validation strategies were sparse and divergent. The validation of FMT capsules is heterogeneous, and processing requires relevant standardisation protocols, mainly focusing on capsule content. Future studies should report validation covariables to enable accurate comparative assessments of clinical effects.